2016
DOI: 10.12693/aphyspola.129.647
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Nano-Crystalline Zirconia Thin Films Prepared at Different Post-Oxidation Annealing Times

Abstract: The zirconia (ZrO2) is one of the transition-metal oxides with most excellent optical properties which thus attracts great attention in optical engineering. A variety of methods were used for deposition of ZrO2 thin films on different substrates. In the present work, homogenous, transparent nanocrystalline zirconia thin films were grown by thermal oxidation of zirconium (Zr) thin films deposited on quartz substrate using DC magnetron sputtering technique. The objective of this study is to reveal the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…According to data from Table I we can observe that the average crystallite size had increased with increase of annealing temperature, which reveals a fine nanocrystalline grain structure. Similar results, showing influence of annealing, were also obtained in [9][10][11] for silver, molybdenum oxide and zirconium oxide thin films. As the annealing temperature was increased the XRD peaks became sharper, which was due to the increase of particle size and due to the enhancement of the crystallinity.…”
Section: Resultssupporting
confidence: 82%
“…According to data from Table I we can observe that the average crystallite size had increased with increase of annealing temperature, which reveals a fine nanocrystalline grain structure. Similar results, showing influence of annealing, were also obtained in [9][10][11] for silver, molybdenum oxide and zirconium oxide thin films. As the annealing temperature was increased the XRD peaks became sharper, which was due to the increase of particle size and due to the enhancement of the crystallinity.…”
Section: Resultssupporting
confidence: 82%
“…The optical spectroscopy results demonstrated that increased doses of UV-A radiation improved the quality of films, in comparison with heat-treated films. In comparison with most of the above cited papers [5,17,[32][33][34], we observed a greater size of grains and greater value in film roughness, leading to greater values in diffuse and haze ratio spectra. In any case, all these features depend on the applied deposition method, as well as the variety and specificity of working conditions.…”
Section: Resultssupporting
confidence: 50%
“…This is explained by the thickness decreasing from 433 nm to 385 nm. In [33], homogenous and transparent nanocrystalline zirconia layers deposited on quartz substrates were produced by thermal oxidation using DC magnetron-sputtering techniques. It is shown that by increasing the annealing time from 60 to 240 min, the grains combine and form larger grains, in this manner changing the surface morphology from a pyramidal to cluster-type surface.…”
Section: Resultsmentioning
confidence: 99%
“…We can observe that the surface morphology of films was highly influenced by O 2 /Ar ratio, dopants and annealing temperatures [3,7,[11][12][13][14].…”
Section: Resultsmentioning
confidence: 96%